2014
DOI: 10.1089/cyber.2012.0537
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Predicted Effect of Social Networking Site Use on Perceived Social Capital and Psychological Well-Being of Chinese International Students in Japan

Abstract: This study investigated how social networking sites (SNSs) use by Chinese international students in Japan influenced their perceived social capital and psychological well-being. In addition, it examined how, as sojourners, Chinese international students' perceived acculturative stress varied. Data were collected from 142 Chinese international students. The results indicated that the intensity of SNS use was unable to predict individuals' perceived social capital and psychological well-being. The effect of SNS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 43 publications
8
107
2
1
Order By: Relevance
“…Further, simply trying to draw linear and/or direct connections between the two constructs could impinge on our understanding and assessment of the influence of SNS. Guo et al (2014) put it aptly, Bthere is no absolute standard to decide whether using SNSs is a good thing because it is not one dimensional^(p.2). Then, a consideration of Bnot [just] the intensity but the functions of SNS use^ (Guo et al 2014, p.4) might provide a broader perspective and, may even help tease apart the mechanics of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Further, simply trying to draw linear and/or direct connections between the two constructs could impinge on our understanding and assessment of the influence of SNS. Guo et al (2014) put it aptly, Bthere is no absolute standard to decide whether using SNSs is a good thing because it is not one dimensional^(p.2). Then, a consideration of Bnot [just] the intensity but the functions of SNS use^ (Guo et al 2014, p.4) might provide a broader perspective and, may even help tease apart the mechanics of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Hinting at the importance of users' active engagement in social networking sites, Burke, Marlow, and Lento [28] demonstrated that greater use of social networking sites is especially associated with increased social well-being, social capital, and reduced loneliness when engagement with Facebook is active rather than passive. Guo, Li, and Ito [29] showed that the usage of social networking sites with a social or informational goal is associated with an increase in perceived bridging social capital as well as increased life satisfaction. Usage with an entertainment goal, however, was not able to predict the perceived social capital and fostered feelings of loneliness.…”
Section: Social Capital and Tie Strength In Online Researchmentioning
confidence: 99%
“…Online social networking may augment the benefits of engaging in faceto-face interaction by extending the reach and accessibility of our social networks [14]. Online social networking is associated with lower levels of loneliness and greater feelings of belonging (social connectedness), social capital, and actual and perceived access to social support and is generally associated with higher levels of life satisfaction and self-esteem [15][16][17].…”
Section: Res Med Eng Scimentioning
confidence: 99%